A Low-Complexity Bit-Plane Entropy Coding and Rate Control for 3-D DWT Based Video Coding - Belyaev, Evgeny; Egiazarian, Karen; Gabbouj, Moncef (IEEE transactions on multimedia, 2013)
This paper is dedicated to fast video coding based on three-dimensional discrete wavelet transform. First, we propose a novel low-complexity bit-plane entropy coding of wavelet subbands based on Levenstein zero-run coder for low entropy contexts and adaptive binary range coder for other contexts. Second, we propose a rate-distortion efficient criterion for skipping 2-D wavelet transforms and entropy encoding based on parent-child subband tree. Finally, we propose one pass rate control which uses virtual buffer concept for adaptive Lagrange multiplier selection. Simulations results show that the proposed video codec has a much lower computational complexity (from 2 to 6 times) for the same quality level compared to the H.264/AVC standard in the low complexity mode.